ChemInform Abstract: Solid Supported 9‐Amino‐9‐deoxy‐epi‐quinine as Efficient Organocatalyst for Stereoselective Reactions in Batch and under Continuous Flow Conditions. Issue 26 (June 2015) - Porta, Riccardo; Benaglia, Maurizio; Coccia, Francesca; Cozzi, Franco; Puglisi, Alessandra
Abstract The general applicability and the recyclability of the novel heterogeneous catalyst are demonstrated by batch reactions between carbonyl compounds and nitroolefins.